Precarious Employment in Present-Day Russia: Relevant Worker Profiles - Nikolaevich Bobkov, Vyacheslav; Gennadievich Odegov, Yuri; Vasilievna Pavlova, Valentina (International Journal of Engineering and Technology, 2018)
This paper provides a characterization of the essence of precarious employment. The author describes some of the key stages in the transformation of the employment sector. The paper shares the findings from a sociological study into precarious employment in a representative group. The author has explored some of the key parameters for the group and has fine-tuned a set of indicators of precarious employment and their quantitative values which identify particular aspects of precarious employment (Note 1), namely with a focus on: assessments of the level of being protected by the employment contract (employee evaluations of the terms and conditions of the employment contract and assessments of the extent to which the employer abides by them; assessments of the likelihood of being laid off; assessments of oneâ€™s willingness to look for another job and the reasons behind it); assessments of the accessibility of mechanisms of social protection for employees; self-assessments of material well-being; work conditions (e.g., length of the work week, half-time work, and availability and duration of work in an additional place); etc. The author has identified a total of 5 profiles for present-day employment in Russia, which are characterized by an increase in signs of precarious employment, and provides a comparative characterization thereof. Â Â Â